2016
DOI: 10.1038/srep28186
|View full text |Cite|
|
Sign up to set email alerts
|

Screening for protein-protein interactions using Förster resonance energy transfer (FRET) and fluorescence lifetime imaging microscopy (FLIM)

Abstract: We present a high content multiwell plate cell-based assay approach to quantify protein interactions directly in cells using Förster resonance energy transfer (FRET) read out by automated fluorescence lifetime imaging (FLIM). Automated FLIM is implemented using wide-field time-gated detection, typically requiring only 10 s per field of view (FOV). Averaging over biological, thermal and shot noise with 100’s to 1000’s of FOV enables unbiased quantitative analysis with high statistical power. Plotting average do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 64 publications
0
70
0
Order By: Relevance
“…When a fluorescent donor experiences FRET, its bulk fluorescence intensity and the lifetime of its excited state decrease. FRET can be used to monitor protein-protein interactions (PPIs) in biological systems such as living cells, tissues, and organisms [74][75][76]. A widely used method to measure FRET is fluorescence lifetime imaging microscopy (FLIM).…”
Section: Choosing the Optimal Fret Reporter Orientation For Estimatinmentioning
confidence: 99%
“…When a fluorescent donor experiences FRET, its bulk fluorescence intensity and the lifetime of its excited state decrease. FRET can be used to monitor protein-protein interactions (PPIs) in biological systems such as living cells, tissues, and organisms [74][75][76]. A widely used method to measure FRET is fluorescence lifetime imaging microscopy (FLIM).…”
Section: Choosing the Optimal Fret Reporter Orientation For Estimatinmentioning
confidence: 99%
“…Another important application of FLI is in the imaging of large tissue at the macroscopic scale (MFLI). The applications hence range from high-throughput in vitro imaging 39 , ex vivo 40 or in vivo tissue imaging 41 for diagnostics, especially within the framework of optical guided surgery 42 , and preclinical studies 43 . Particularly, there is great interest in employing NIR MFLI as in this spectral window the background fluorescence is reduced, and deep tissue imaging can be performed with high sensitivity.…”
Section: Macroscopic Fluorescence Lifetime Imaging (Gated Iccd)mentioning
confidence: 99%
“…Currently most in-cell studies of proteins' structure employ nuclear magnetic resonance (NMR), or fluorescence spectroscopy (5,22), each method having its advantages and limitations. In-cell FRET (Förster energy transfer) is effective for monitoring protein-protein interactions, determining dissociation constants and identifying conformational changes of appropriately fluorophore-labeled target proteins (23)(24)(25). In addition, fluorescence correlation spectroscopy (FCS) can be used determine dissociation constants of protein oligomers in cells (26).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, many proteins display poor in-cell NMR signal qualities (line broadening) due to restricted motions and transient interactions with cellular components (3,32,33). In-cell studies using NMR and fluorescence techniques reported on protein folding and stability in cells (17,24,(34)(35)(36)(37)(38)(39)(40), structural changes of disordered proteins (41)(42)(43) and, to some extent, on protein association e and the stabilization of oligomeric protein forms (23,25,26). EPR (electron-paramagnetic resonance)-based double electron-electron resonance (DEER, also called PELDOR) spectroscopy has been suggested as an attractive alternative method to interrogate protein structures in cells (21,42,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Introductionmentioning
confidence: 99%